Zaburzenia ze spektrum autyzmu – analiza różnic i podobieństw głównych nurtów terapeutycznych behawioralnego, poznawczego i neurorozwojowego w praktyce edukacyjne - Bombińska-Domżał, Anna (Annales Universitatis Paedagogicae Cracoviensis Studia Paedagogica, 2021)
The article attempts to analyze therapeutic processes aimed at children and adolescents with autism spectrum disorder preferred in the process of special, integration and inclusion education, resulting from three main currents in psychology: behavioral, cognitive and neurodevelopmental. On the foundations of these currents there arose various ways of understanding the essence of autism, but also different theories and therapeutic models built around other learning mechanisms and aimed at differently defined therapy goals. The article, apart from presenting the main assumptions of various therapeutic schools, looks for possible common points justifying the eclectic approach in education and therapy of students with autism based on Evidence-Based Practice